Superhydrophilic nickel cyclotetraphosphate for the hydrogen evolution reaction in acidic solution. Issue 36 (2nd September 2021) - Wang, Kaili; Sun, Xiujuan; Huang, Wen; Cao, Qiuhan; Zhao, Yongjie; Ding, Rui; Liu, Enhui; Gao, Ping; Lin, Weiwei
Abstract : Ni2 P4 O12 /CC with mesoporous characteristics and a superhydrophilic surface demonstrates excellent catalytic activity toward the acidic hydrogen evolution reaction (HER). Abstract : Nickel cyclotetraphosphate grown on carbon cloth (Ni2 P4 O12 /CC) is synthesized via an anion exchange reaction method and it shows excellent hydrogen evolution reaction (HER) activity and strong working stability in acid due to the merits of its unique polymer-like structure, mesoporous characteristics, and superhydrophilic surface.